Improvement in angina pectoris after percutaneous coronary interventions in focal and diffuse coronary artery disease. (3rd October 2022) - Munhoz, D; Collet, C; Collison, D; Mizukami, T; McCartney, P; Sonck, J; Ford, T; Berry, C; De Bruyne, B; Oldroyd, K
Abstract: Objective: To investigate the effect of PCI on patient-reported outcomes in focal and diffuse coronary artery disease (CAD) as defined by the pullback pressure gradient (PPG). Background: Improvements in fractional flow reserve (FFR) following PCI are associated with freedom from angina. CAD patterns influence the FFR change after stenting. Therefore, CAD patterns might be essential to assess the likelihood of PCI success in terms of angina relief. Methods: This is a sub-analysis of the TARGET-FFR randomized clinical trial (NCT03259815). The 7-item Seattle Angina Questionnaire (SAQ-7) and EuroQol five-level EQ-5D questionnaire (EQ-5D-5L) were administered at baseline and three months after PCI. The PPG index was calculated from manual pre-PCI FFR pullbacks and the median PPG value was used to define focal and diffuse CAD. Results: 103 patients (51 with focal and 52 with diffuse disease) were analyzed. There were no differences in baseline characteristics between patients with focal and diffuse CAD. Patients with focal disease had larger increases in FFR with PCI than those with diffuse disease (0.30±0.14 units vs 0.19±0.12 units, p<0.001). Patients who underwent PCI to focal CAD had significantly higher SAQ-7 summary scores at follow-up compared to those with diffuse CAD (87.1±20.3 vs. 75.6±24.4, mean difference 11.5 [95% CI 2.8 to 20.3], p=0.01). Following PCI, residual angina was present in 39.8% of all patients but was significantly lower among those with treated focal CAD (27.5% vs 51.9%, p-value=0.020). Conclusion: Persistent angina after PCI was almost twice as common in patients with diffuse CAD as defined by the pre-PCI PPG. Patients with focal disease reported greater improvement in angina and quality of life with PCI. The likelihood of successful angina relief from PCI can be predicted by the baseline pattern of CAD. Funding Acknowledgement: Type of funding sources: None.